A Study on Investors’ Perceptions towards Stock Market - Kok Ban Teoh; Camilo Pérez-Restrepo; Carolina Ardila López; Sharmila Thulasedass; Chetana S; Padmalini Singh; Elyoni Inez Sandra Suardi; Dwi Nita Aryani; Juhi Aggarwal; Abhijit Das (International Journal of Accounting & Finance in Asia Pasific (IJAFAP), 2021)
The stock market occurs from the interaction of a group of buyers (investors) and sellers of shares (companies), who represent ownership of the business. This includes a security listed on a public stock exchange under government supervision. Shares or stock market can be classified according to the country where the company is domiciled, for example Gudang Garam (company in Indonesia) which is domiciled in Indonesia and traded on the Indonesia Stock Exchange. The stock market has become an attractive and profitable investment today for investors and the stock market has grown rapidly over the years and is getting more and more attention because it deals with the future of money. However, a lot of investors are still worried to invest in stock market today, even investing in stock market results a huge profit. This reason can be the volatility in stock market. Therefore, this study focused on the investors’ perceptions towards stock market in different geographical areas. The data collected through online interview and distributing questionnaires to respondents in order to understand their behaviors, attitudes, desires, perspectives and level of awareness towards the stock market. The results showed that investors’ perceptions on buying shares in Asia are represented by several indicators, such as neutral information, accounting information, and social relevance, in which these three indicators generate impressions of the company’s activities based on profits and fundamental thinking patterns. Therefore, this will have an influence on investors in making decisions on the shares which will be chosen by them in the future.